Liver Necrosis and Lethal Systemic Inflammation in a Murine Model of Rickettsia typhi Infection: Role of Neutrophils, Macrophages and NK Cells. - Stefanie Papp; Kristin Moderzynski; Jessica Rauch; Liza Heine; Svenja Kuehl; Ulricke Richardt; Heidelinde Mueller; Bernhard Fleischer; Anke Osterloh (Public Library of Science (PLoS), 2016)
Rickettsia (R.) typhi is the causative agent of endemic typhus, an emerging febrile disease that is associated with complications such as pneumonia, encephalitis and liver dysfunction. To elucidate how innate immune mechanisms contribute to defense and pathology we here analyzed R. typhi infection of CB17 SCID mice that are congenic to BALB/c mice but lack adaptive immunity. CB17 SCID mice succumbed to R. typhi infection within 21 days and showed high bacterial load in spleen, brain, lung, and liver. Most evident pathological changes in R. typhi-infected CB17 SCID mice were massive liver necrosis and splenomegaly due to the disproportionate accumulation of neutrophils and macrophages (MΦ). Both neutrophils and MΦ infiltrated the liver and harbored R. typhi. Both cell populations expressed iNOS and produced reactive oxygen species (ROS) and, thus, exhibited an inflammatory and bactericidal phenotype. Surprisingly, depletion of neutrophils completely prevented liver necrosis but neither altered bacterial load nor protected CB17 SCID mice from death. Furthermore, the absence of neutrophils had no impact on the overwhelming systemic inflammatory response in these mice. This response was predominantly driven by activated MΦ and NK cells both of which expressed IFNγ and is considered as the reason of death. Finally, we observed that iNOS expression by MΦ and neutrophils did not correlate with R. typhi uptake in vivo. Moreover, we demonstrate that MΦ hardly respond to R. typhi in vitro. These findings indicate that R. typhi enters MΦ and also neutrophils unrecognized and that activation of these cells is mediated by other mechanisms in the context of tissue damage in vivo.